Dietary habits during the COVID-19 pandemic. Are work environments part of the problem? - Tiboni-Oschilewski, Ornella; Perez-Silva, Rodrigo; Biasini, Beatrice; Scazzina, Francesca (Frontiers in Sustainable Food Systems, 2022)
The COVID-19 pandemic pushed a large number of workers out of their offices and to their homes for a significant period of time for teleworking. However, some workers continued to work in their offices and others went home only partially. This arguably exogenous shock to the way in which workers performed their jobs opened the opportunity to evaluate whether work environments are ideal for promoting healthier diets and reducing overweight among office workers. We explore the results of two consecutive surveys (pre- and during-COVID-19) to examine whether workers working from home perceived their situation as more favorable in terms of healthy eating habits and weight gains. Our results show that workers did perceive their homes as places where they can follow healthier eating habits, but this was not accompanied by weight loss. On the contrary, workers fully teleworking were more likely to perceive weight gains and diet-related health problems than their in-office counterparts. Among teleworkers, those only partially teleworking were the most affected. This study opens many questions about food environments at work that remain unanswered. More studies in this area are needed to understand how the food at work affects the worker's health.